Encounter With a Selfish Virus Sabotages Its Vector to Orient Toward Requisite Host Plant: A Case Study With Chili Leaf Curl Virus-Whitefly - Yadav, Rajeev Kumar; Kambham, Madhavi Reddy; Parepally, Saravan Kumar; Vyas, Meenal; Manem, Krishna Reddy; Kamala Jayanthi, Pagadala Damodaram (Frontiers in Ecology and Evolution, 2022)
Interactions of a virus with its vector and host plant have challenged entomologists, pathologists and biologists alike. Phytophagous insects depend on specific host volatile cues to locate suitable host plants for feeding and oviposition. Several studies have revealed that plant viruses modify their insect vector’s orientation towards specific host plants to facilitate their spread and survival. The ecological and molecular basis of this vector behaviour modification remains largely unknown and was therefore explored in this study. Interestingly, host volatile preference for non-viruliferous female whiteflies [Bemisia tabaci (Genn.)] was found to be preferentially oriented towards infected chilli plant [with chilli leaf curl (ChCLV)] volatiles, while viruliferous whiteflies preferred healthy chilli plant (Capsicum annum L.) volatiles in olfactometer. The electrophysiological studies involving electroantennogram (EAG) assays exhibited similar trend in EAG response amplitudes. Gas Chromatography linked electroantennodetection (GC EAD) revealed specific plant volatile cues responsible for altered host orientation behaviour of the vector. Transcriptome profiling of the viruliferous and non-viruliferous whiteflies and realtime qPCR validation showed differential expression of certain odorant binding proteins (OBPs) in viruliferous whiteflies. Our results suggest that there is a plant virus mediated altered chemoecological behaviour in the vector with respect to orientation towards its host plant. Based on the findings we speculate that the virus mediates such change in the vector for a continued transmission success to the host.